Pro Apache Ant - Moodie, Matthew (Apress : Imprint: Apress, 2006)
Pro Apache Ant is ideal for Java developers who need to use the leading open source build tool out there for development and project management. It is organized around chronological tasks instead of alphabetical functions, using a sample application throughout the set-up, from calling database scripts to unit testing. Practical examples are used at every stage and each task includes a concrete example. The configuration files are XML based, so there's no need for you to write shell commands. Each task is run by an object that implements a particular task interface. And if you really need to execute a shell command, Ant has a task that allows different commands based on the operating system.